Differential Equations : a linear algebra approach - Dey, Anindya (Boca Raton: CRC Press, 2022)
Differential Equations: A Linear Algebra Approach follows an innovative approach of inculcating linear algebra and elementary functional analysis in the backdrop of even the simple methods of solving ordinary differential equations. The contents of the book have been made user-friendly through concise useful theoretical discussions and numerous illustrative examples practical and pathological.
Anindya Dey is Assistant Professor in the Department of Mathematics, St Xaviers Colleges, Kolkata.
Keywords: Differential equations; Algebras, Linear; Algebras, Linear; Differential equations